2004
DOI: 10.1080/09658210344000468
|View full text |Cite
|
Sign up to set email alerts
|

Providing misleading and reinstatement information a year after it happened: Effects on long‐term memory

Abstract: The question addressed here is whether misleading suggestions made to children a year after target events had occurred will alter long-term recall. One group (3-13 years old when injured and treated in a hospital Emergency Room) were given both misleading and accurate reinstating information a year later, and recall of target events assessed both 1 week and another year later (i.e., 2 years post-injury). A control group had recall assessed both 1 and 2 years post-injury. Misleading had little effect on childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
18
2
2
Order By: Relevance
“…Our results are opposite to those obtained in studies on the misinformation effect (Loftus et al, 1978;Peterson et al, 2004). This may be due to the importance of the discussion.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Our results are opposite to those obtained in studies on the misinformation effect (Loftus et al, 1978;Peterson et al, 2004). This may be due to the importance of the discussion.…”
Section: Discussioncontrasting
confidence: 57%
“…Two experiments investigating the misinformation effect, in which misleading information was provided in a different way than during an interaction between people, dealt with this problem (Loftus, Miller, & Burns, 1978;Peterson, Parsons, & Dean, 2004). The results of these studies suggested that a longer time delay between introducing misinformation and memory test resulted in a slight decrease in the number of answers consistent with the misleading information.…”
mentioning
confidence: 87%
“…This prediction can be drawn because of two reasons. First, repeated retrieval is a powerful memory enhancer, and eyewitnesses are more likely to resist misinformation when the original memory is stronger (Loftus, 1979;Marche, 1999;Peterson, Parsons, & Dean, 2004); therefore, recalling details of an event multiple times may lead to a reduction in later suggestibility. Second, one component of the cognitive interview involves repeated retrieval.…”
Section: Repeated Testing and Eyewitness Memorymentioning
confidence: 99%
“…Jest to efekt odwrotny do tego, jaki uzyskano w badaniach nad dezinformacją, której wpływ z czasem słabnął (Loftus i in., 1978;Peterson i in., 2004). Byü moĪe wynika to ze znaczenia samej rozmowy.…”
Section: Dyskusja Wynikówunclassified
“…Analizowano go jednak w eksperymentach nad efektem dezinformacji, w których niezgodną ze zdarzeniem informacjĊ podaje siĊ w inny sposób niĪ podczas rozmowy. Wyniki tych badaĔ sugerują, Īe wraz z wydłuĪeniem czasu miĊdzy podaniem dezinformacji a testem pamiĊci, osoby badane nieco rzadziej udzielają odpowiedzi zgodnych z dezinformacją (Loftus, Miller i Burns, 1978;Peterson, Parsons i Dean, 2004). Byü moĪe upływający czas miĊdzy rozmową o zdarzeniu a póĨniejszym jego przypominaniem takĪe bĊdzie powodował zmniejszenie włączania do relacji pamiĊciowych błĊdnych informacji uzyskanych w dyskusji.…”
unclassified